Pendampingan Guru TPQ Al Ikhlas Desa Sidorejo Pagelaran Kab. Malang dalam Pembuatan Media Pembelajaran Kreatif Berbahasa Indonesia untuk Anak-Anak - Malikha, Usrin (Jurnal Aksi Afirmasi, 2025)
This community service program focuses on assisting teachers at TPQ Al Ikhlas in Sidorejo Village, Pagelaran District, Malang Regency, in creating creative learning media in the Indonesian language for children. The goal of this initiative is to enhance the teaching process by providing teachers with practical skills to design engaging and interactive educational tools. These tools include posters, flashcards, and simple digital media that are tailored to improve children’s understanding of both religious and general knowledge. The program consists of workshops and direct mentoring to help teachers develop creative materials that can stimulate the children's interest in learning. Teachers are trained to integrate these materials into their daily lessons, making learning more enjoyable, dynamic, and effective. Through this project, teachers not only enhance their creativity but also improve their ability to engage children in a fun and meaningful way. The expected outcome is an improvement in the quality of education at TPQ Al Ikhlas, contributing to a more effective learning environment for children. This program aims to have a lasting positive impact by empowering teachers and enriching the learning experience, ultimately benefiting the cognitive and academic development of the children.